UOJM editor training: results from the 2013 editor satisfaction survey and highlights from 2013-2014 training workshops - Suen, Colin; Cheung, Loretta (Université d'Ottawa | University of Ottawa, 2014)
BACKGROUND UOJM recognizes that editor competency and preparedness directly impacts the quality of peer review, which holds the key to producing a great publication. We believe that success of our journal is based on a central goal of promoting physician competency in medical communication and developing leaders in medicine. In the age of evidence-based medicine, there are surprisingly few, if at all, opportunities for medical trainees to gain formal training in scientific writing and critical appraisal. Over the last two years, the UOJM has aimed to address these gaps and worked on developing a training program to equip participants with these important skills. Indeed, the merits of involvement in a peer reviewed journal at this stage of medical/research training have been recognized by its trainee participants, and have been reviewed extensively by Kevin Lee [1]. Following the success of the 2013 issue, UOJM made considerable strides to further improve the quality of content in the journal. In 2012-2013, 30 students participated as reviewers on the editorial board and received a practical experience in peer reviewed research. We conducted a year-end survey to identify issues and areas for improving the editor experience.
Keywords: Editor training; peer review; Medical Education; critical appraisal; medical journal; editorial